PHILOS Plate as a Fixation of Proximal Humeral Fracture: A Revisit - Mohd Shaffid Md Shariff; Firdaus Hayati; Nornazirah Azizan; Affirul Chairil Ariffin; Hanizah Ngadiron (Universiti Malaysia Sabah, 2024)
Indexed by MyCite